SIRT1 prevents pulmonary thrombus formation induced by arachidonic acid via downregulation of PAF receptor expression in platelets. (16th November 2016) - Kim, Yun Hak; Bae, Jin Ung; Kim, In Suk; Chang, Chulhun L.; Oh, Sae Ock; Kim, Chi Dae
Abstract: SIRT1, a class III histone deacetylase, is critically involved in cellular response to stress and modulates cardiovascular risk factors. However, its role in thrombus formation is largely unknown. Thus, this study investigated the effect of SIRT1 on pulmonary thrombus formation, and then identified its role in the modulation of platelet aggregation. In isolated human platelets, cell aggregation was increased by various platelet activators, such as platelet activating factor (PAF), arachidonic acid (AA), ADP, and thrombin. AA- and PAF-mediated platelet aggregations were suppressed by WEB2086, a PAF receptor (PAFR) antagonist. Pulmonary thrombus formation induced by PAF or AA was also attenuated by WEB2086, suggesting that PAFR plays a key role in AA-induced platelet aggregation. In platelets isolated from SIRT1-TG mice as well as in platelets treated with resveratrol or reSIRT1, PAFR expression was decreased, whereas this expressional downregulation by SIRT1 activators was inhibited in platelets treated with MG132 (a proteasome inhibitor) or NH4 Cl (a lysosome inhibitor). Furthermore, platelet aggregation induced by AA was markedly attenuated by resveratrol and reSIRT1. Likewise, the increased pulmonary thrombus formation in mice treated with AA was also attenuated by SIRT1 activators. In line with these results, pulmonary thrombus formation was markedly attenuated in SIRT1-TG mice. Taken together, this study showed that SIRT1 downregulates PAFR expression on platelets via proteasomal and lysosomal pathways, and that this downregulation inhibits platelet aggregation in vitro and pulmonary thrombus formation in vivo .